2020
DOI: 10.1111/anae.15170
|View full text |Cite
|
Sign up to set email alerts
|

Risks to healthcare workers following tracheal intubation of patients with COVID‐19: a prospective international multicentre cohort study

Abstract: Healthcare workers involved in aerosol-generating procedures, such as tracheal intubation, may be at elevated risk of acquiring COVID-19. However, the magnitude of this risk is unknown. We conducted a prospective international multicentre cohort study recruiting healthcare workers participating in tracheal intubation of patients with suspected or confirmed COVID-19. Information on tracheal intubation episodes, personal protective equipment use and subsequent provider health status was collected via self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
291
2
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(309 citation statements)
references
References 18 publications
6
291
2
10
Order By: Relevance
“…When each contact with a patient becomes a potential health risk, supervised procedures performed by a trainee may seem unnecessary. Aerosol-generating procedures such as bag and mask ventilation, tracheal intubation, and tracheostomy appear to carry the greatest risks, 3 and there is understandable pressure for the most experienced practitioner to perform the procedure swiftly and efficiently. This diminishes the experience gained by the trainee and the opportunity to be signed off for a workplace-based assessment.…”
Section: Clinical Teachingmentioning
confidence: 99%
“…When each contact with a patient becomes a potential health risk, supervised procedures performed by a trainee may seem unnecessary. Aerosol-generating procedures such as bag and mask ventilation, tracheal intubation, and tracheostomy appear to carry the greatest risks, 3 and there is understandable pressure for the most experienced practitioner to perform the procedure swiftly and efficiently. This diminishes the experience gained by the trainee and the opportunity to be signed off for a workplace-based assessment.…”
Section: Clinical Teachingmentioning
confidence: 99%
“…El-Boghdadly et al found that approximately one in ten healthcare workers involved in tracheal intubation of patients with or suspected of COVID-19 subsequently reported symptoms or laboratory-confirmed COVID-19 diagnosis. 15 That study reported 5,148 intubation episodes across 17 countries involving assistants and intubators and acknowledge that the exposure source may not just be attributed to the tracheal intubation episode. Despite our MERIT members being exposed to multiple intubations, the rate of healthcare workers self-isolating because of suspected or confirmed COVID-19 is similar to that reported by El-Boghdadly et al That said, the utilization of adequate PPE was greater in this current study compared with the data presented by El-Boghdadly et al; thus, one might expect the rates of COVID-19 transmission to healthcare workers to be lower in our institutional cohort.…”
Section: Discussionmentioning
confidence: 99%
“…MERIT was designed to be a self-sufficient, rapidly mobile team, thus all team members had their own PPE available for every airway procedure they attended, including fit-tested FFP3 respirators, visors, long-sleeved gowns, and gloves. 14 A single-use videolaryngoscope was the tracheal intubation device of choice, 15 and included either the iview videolaryngoscope (Intersurgical Ltd., Wokingham, UK) or the AirtraqÒ (Fannin, Dublin, Ireland). The videolaryngoscope was chosen because it potentially reduces the time to tracheal intubation, improves the first pass success rate, allows all team members to observe the laryngoscopic view, and increases the distance between the laryngoscopist and patient thereby reducing the risk of aerosol or droplet exposure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 11 May 2020, 203 healthcare worker deaths had been reported in the UK [3]. Whilst none of these were anaesthetists or intensivists, 53 out of 1718 (3.1%) healthcare workers performing or involved in tracheal intubation of patients with confirmed or suspected COVID‐19 subsequently reported laboratory‐confirmed SARS‐CoV‐2 infection [4].…”
Section: Introductionmentioning
confidence: 99%